OPTIMIZATION IN USING ONLINE LEARNING MEDIA DURING THE COVID-19 PANDEMIC AT SMKN 2 INDRAMAYU - Huwaidi, Fahmi; Nandiyanto, Asep Bayu Dani; Azis, Ghani; Pratama, Muhammad Fawwaz wahyu (Universitas Pendidikan Indonesia, 2021)
WHO (World Health Organization) has designated Covid-19 as a global pandemic, because it has the opportunity to infect populations worldwide. Therefore, in an effort to break the chain of the spread of Covid-19, the Minister of Education and Culture issued a learning regulation during the pandemic, namely the learning process carried out remotely from home through online learning. This makes the use of social media or video conferencing an urgent matter to replace the usual face-to-face learning system. Effectiveness and student understanding are the main focus in this research to create effective, innovative, and creative online learning.